(untitled) (Delta Medical College Journal, 2016)
Background: Hanging is one of the common methods of suicide in the world. The rate of suicide by hanging is increasing day by day in Bangladesh. Suicide by hanging is the act of intentionally killing oneself by suspension from an anchor point or ligature point (e.g., an over head beam or hook) by a ligature or jumping from a height with a noose around the neck. Hanging is a very simple method of suicide that does not require complicated techniques. The materials required are easily available, and a wide range of ligature can be used, so most of the people commit suicide by suspension from a height with a ligature around the neck. Objective: The objective of this study was to find out demography of hanging, its distribution according to age group, sex, common ligature materials used by victims, observed post mortem findings and in this way try to identify the causative factors and develop the preventive measures that are essential to reduce death due to hanging. Materials and method: A retrospective study was done on the basis of 3rd copies of postmortem reports preserved in the department of Forensic Medicine, Dhaka Medical College, Dhaka, Bangladesh for the period of 2 years, (from January 2008 to December 2009) with the permission of the autopsy surgeons. Results: Out of 574 cases, 159 (27.71%) were male and 415 (72.29%) female. Among them 304 (52.96%) were married and 270 (47.04%) were unmarried. Most of the victims (46.86%) were from the age group 21-30 years. Dopatta (orna) was the commonest (41.28%) ligature material. Conclusion: To reduce the number of suicide by hanging a well designed and comprehensive programme is needed, which will identify the causative factors and which might help in prevention of suicidal hanging. Delta Med Col J. Jan 2016 4(1): 9-12